Investigation of Screen Time and Symptom Severity in Children with Autistic Spectrum Disorder - Kevser Nalbant; Semih Erden (Çocuk Dergisi)
Objective: Screen-based media (e.g. television, computer, cell phone, tablet) has become an increasingly important part of our life. Children with autism spectrum disorder (ASD) are known to be interested in limited subjects and highly attracted to screens. The purpose of this study is to investigate the time of screen use in newly diagnosed children with ASD and the association between screen time and symptom severity of ASD. Methods: The symptom severity of ASD was determined using the Childhood Autism Rating Scale. Information concerning socio-demographic characteristics, clinical data, and frequency and duration of children’s screen exposure since birth were collected during clinical interviews from the primary caregivers. Linear regression analysis was performed to examine the associated factors on symptom severity of ASD. Results: In our study, it was found that children with ASD use screens at an earlier age and for a longer period of time when compared to the recommendations of the American Academy of Pediatrics. Also, our results indicated that longer daily screen time and longer periods of no interaction during screen time <24 months, >1 h ⁄ day were associated with the symptom severity of ASD. Discussion: This study suggests that longer daily screen time in early childhood might increase the symptom severity of ASD. These results support that appropriate guidance and education for parents on how to optimize the benefits and potential harms of screen use may be a substantial preventive mental and public health service to support the socio-emotional development for early childhood.